Dynamic characteristics analysis of asynchronous motorized spindle considering combined unbalanced magnetic pull and nonlinear bearing restoring force effects. (15th February 2023) - Hao, Jin; Yao, Zhenghong; Li, Changyou; Song, Wenjun; Miao, Huihui; Xu, Mengtao; Liu, Zhendong
Abstract: The built-in motor of the motorized spindle is the key to realizing its movement. However, the unbalanced magnetic pull (UMP) generated in the built-in motor seriously affects its dynamic stability. In this work, a generalized time-varying dynamic model of the motorized spindle is proposed to evaluate the effect of dynamic loads on the spindle system. The external dynamic loads on the spindle mainly include the UMP generated by the built-in motor, the nonlinear restoring force of the bearing, and the eccentric excitation of the system mass. Considering the change of magnetic path caused by the dynamic displacement of the rotor, the radial and axial projection model and additional torque model of UMP are proposed. Numerical simulations are employed to handle the dynamical equation containing the time-varying UMP function. Based on the simulation results, the effects of built-in motor parameters, bearing parameters, rotor static eccentricity, and other factors on the dynamic characteristics of the spindle system are analyzed. The numerical results of the vibrations are verified experimentally.